A New technology of transformer bushing state detection based on transient dielectric response. Issue 1 (1st March 2023) - Sun, Lei; Zhang, Lu; Jing, Feng; Ma, Li; Wang, Wensen; Jin, Jiandong
Abstract: Failure of the transformer bushing will cause the transformer to be powered down or damaged, affecting the safe operation of the power system. This paper proposes a method using system harmonics as the dielectric response excitation source and studies the transformer bushing insulation online detection technology based on transient dielectric response characteristics. The technical scheme and system structure of the online monitoring technology of transformer bushing insulation based on dielectric response characteristics are given. A calculation model of short-circuit grounding and capacitor switching of a 35kV substation was established, and the harmonic frequency content and amplitude distribution of grid disturbance were analyzed. A case of dielectric response measurement of the bushing is given. The research shows that the system will generate overvoltage in short circuit grounding, capacitor switching, etc. The system harmonic frequency is in the range of the dielectric response test frequency band (1Hz~1kHz), and the harmonic amplitude is also large, which can be used as an excitation source. The excitation source of the dielectric response test causes a change in the dielectric response of the transformer bushing and acts as a "probe" that reflects the insulation state of the bushing. The medium and high-frequency bands of the dielectric spectrum in the frequency domain are also sensitive to moisture, which can be used to diagnose the insulation state of the bushing.